Evaluation of Changes in Renal Function of Pregnant Women with Preeclampsia in Al-Jabal Al-Akhdar - Salma Hamed; Taweda Khalifa; Fareda Mekal; Marfoua Ali (AlQalam Journal of Medical and Applied Sciences, 2022)
Preeclampsia is a multifactorial condition characterized by a constellation of signs and symptoms, including the new onset of hypertension and proteinuria during the last trimester of pregnancy. Women with preeclampsia diagnoses have an increased risk of developing renal diseases later in life. This study was aimed at evaluating serum uric acid, serum creatinine and serum urea in preeclamptic women and comparing values to normal pregnancy women. A total of 100 pregnant women were enrolled in this study. Out of 40 normal pregnant women, 60 suffered from preeclampsia. Blood samples were collected in a plane test tube for the assay of urea, creatinine and uric acid levels. Levels of serum urea and uric acid were increased significantly in the preeclampsia group (29.6 ± 13.8 & 5.80 ± 1.13) compared to the control group (20.50 ± 2.70& 2.982 ± 0.672) respectively. Meanwhile, the level of serum creatinine was increased without any significant differences between the preeclampsia group (0.842 ± 0.346) and the control group (0.798 ± 0.312). Results found a positive association (p<0.000) between serum creatinine and serum urea. We conclude from this study that preeclampsia has deleterious effects on renal function as shown by alteration of (serum urea and serum uric acid). These parameters can be taken as predictors of the disease. Therefore, assessment of these parameters helps in monitoring the function of the kidney in preeclampsia.